2016
DOI: 10.1002/j.0022-0337.2016.80.12.tb06229.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Model for Training in Periodontal Examinations Using Manikins

Abstract: The aim of this study was to develop and test models for training dental students in periodontal examinations using manikins that had distinct anatomical designs but were indistinguishable in external appearance. After four models were tested for inter-and intra-examiner reliability by two experienced dentists, 26 additional models were produced. The models were tested by 35 dental students at a dental school in Germany in 2014. The testing involved completing a periodontal examination that included probing de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
0
14
0
2
Order By: Relevance
“…[12][13][14] However, 2 other studies concluded that although students had a positive reaction to TEL, they still preferred the traditional learning methodology. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] All 7 studies assessed knowledge gain at level 2 (learning); however, educational tools differed among the studies. Two studies applied practical exams 13,23 ; 2 applied multiplechoice questions (MCQ), 14,15 1 applied a writing test, 12 and 2 applied educational tool combinations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] However, 2 other studies concluded that although students had a positive reaction to TEL, they still preferred the traditional learning methodology. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] All 7 studies assessed knowledge gain at level 2 (learning); however, educational tools differed among the studies. Two studies applied practical exams 13,23 ; 2 applied multiplechoice questions (MCQ), 14,15 1 applied a writing test, 12 and 2 applied educational tool combinations.…”
Section: Resultsmentioning
confidence: 99%
“…15 However, other studies questioned the capability of conventional learning methods in offering a more in-depth learning experience for students and suggest that more simulation and innovative learning methods would improve educational outcomes in periodontics. [16][17][18][19][20] Nonetheless, despite reports about the positive effects of TEL in improving educational outcomes in periodontics education, 13,[21][22][23] Ramlogan et al highlighted that the exclusive use of video as a TEL had some limitations. 12 Furthermore, corroborating with Levine et al, some authors did not find a difference in TEL application to traditional learning methods in improving educational outcomes of undergraduate dental students' in periodontics.…”
Section: Introductionmentioning
confidence: 99%
“…Entre a aplicação inicial e após a fase laboratorial o aumento desses quesitos esteve entre 11,2 e 49,6 pontos, enquanto a evolução entre as aplicações após fase laboratorial e após fase clínica variou entre 2,2 e 18,7. Resultados semelhantes foram observados em outras pesquisas, que apontaram que a simulação não é alicerce para afirmar que os estudantes estão prontos para trabalhar com situações clínicas reais sem maiores intercorrências, porém é capaz de prover maior segurança e autonomia quando da exposição a um cenário verdadeiro 2,3,[11][12][13][14] .…”
Section: Discussionunclassified
“…In the past, dental students have been trained either on manikins, dental models, or directly on patients for periodontal examination, scoring, and indexing procedures (Heym et al, 2016 ). Students have often found difficulties, leading to patient discomfort such as pain and bleeding while probing the patients for examination (Heym et al, 2016 ). Hence, it would be a good approach to print 3D models simulating gums, periodontal tissues, and defects with respective tissue characteristics to develop the correct proprioception and skill before operating the patient.…”
Section: Periodonticsmentioning
confidence: 99%